1998
DOI: 10.1021/ac980289r
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ionization-Ion Trap Mass Spectrometry for Structural Analysis of Complex N-Linked Glycoprotein Oligosaccharides

Abstract: Electrospray ionization-ion trap mass spectrometry, with its capacity to perform multiple stages of fragmentation (MSn), is demonstrated as an effective method for the structural characterization of permethylated N-linked complex glycoprotein oligosaccharides. Complex glycan structural features, such as N-acetyllactosamine antenane, neuraminic acids, and nonreducing terminal GlcNAc monosaccharides, commonly suppress cross-ring and core saccharide cleavages in traditional MS/MS experiments. Using ion trap mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
122
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 21 publications
(34 reference statements)
2
122
0
Order By: Relevance
“…In these examples, we will use many of the concepts and tools previously described. 7,8,15,[26][27][28] All structures were derived de novo with input data from a single instrument.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these examples, we will use many of the concepts and tools previously described. 7,8,15,[26][27][28] All structures were derived de novo with input data from a single instrument.…”
Section: Resultsmentioning
confidence: 99%
“…6 In both cases, however, the product structures remain to be characterized. A large body of work has shown that spectral comparisons of isomers at different stages of sequential molecular fragmentation (MS n ) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] are clearly different, although in one case, reproducibility has been reported to be "vague". 25 In our experience, spectral reproducibility has been excellent, 26 and this very feature has provided an opportunity to build a searchable fragment library 27 and derive glycan structure with supporting tools.…”
mentioning
confidence: 99%
“…TOF/TOF or Q-TOF mass spectrometers have been widely used in tandem MS characterization of oligosaccharides. In contrast to such tandem-in-space types of instruments, where tandem MS is limited to a MS 2 stage (not including in-source fragmentation), ion storage devices, such as ion trap mass spectrometers, allow multi-stage activations of the parent oligosaccharide ions into successive fragment ions [13,[47][48][49]. Sequential fragmentation, analogous to successive enzyme treatment in the classic sequencing technique, is thus possible with ion trap instruments.…”
mentioning
confidence: 99%
“…Due to the poor basicity of glycans, formation of sufficient MH ϩ ion abundance in positive mode ESI is difficult to achieve [13][14][15][16]. Negative mode ESI offers ionization advantages for the analysis of glycans, however, positive mode ESI is also desirable due to its capability to generate different MS/MS glycan ion fragmentation than typically observed in negative mode ESI-MS/MS [17,18]. To improve positive mode ESI ionization of glycans, derivatization of glycans with molecules containing basic sites has been employed [19].…”
mentioning
confidence: 99%